Nanostructured hybrid sol-gel coatings for surface protection
By using a composition of methacrylate silane and zirconium alkoxide complex to form a zirconium-based mixed sol-gel coating with high adhesion and density, metal surface coatings in the prior art are solved in acidic and neutral. The corrosion resistance and poor adhesion problems in humidity environments achieve transparent, durable and beautiful coating effects.
Patent Information
- Application Number
- CN202080030193.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-21
- Filing Date
- 2020-02-20
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-02-20
AI Technical Summary
Existing metal surface coatings are difficult to meet the high corrosion resistance, barrier properties, adhesion and UV resistance at the same time, especially in acidic and neutral humidity environments, and are prone to poor adhesion during use.
A composition of methacrylate silane and zirconium alkoxide complex is used to form a transparent zirconium-based mixed sol-gel coating, which enhances adhesion and density through tridentate silanes, providing high adhesion and heat resistance.
It achieves a comprehensive anti-corrosion, durability and aesthetic coating on metal surfaces, with high corrosion resistance, barrier properties and UV resistance, improving adhesion and coating density.
Smart Images

Figure CN113939360B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to nanostructured hybrid sol-gel coatings for surface protection. Background of the Invention
[0003] The present invention is particularly suitable for providing coatings on metal surfaces, however it will be appreciated that the coatings of the present invention may also be used on plastic surfaces, including metal-coated plastic surfaces and 3D printed / additively manufactured products.
[0004] Metals are used as structural materials in many industries, including construction, mechanical and electrical engineering, transportation and medical. The most commonly used metals are iron, aluminum, copper, titanium and zinc.
[0005] Iron is the second most abundant metal in the Earth's crust after aluminum, and its production exceeds that of all other metals combined. 98% of iron is used to make various forms of steel (stainless steel, mild steel, and others), mainly used in the construction, engineering, and transportation industries. World steel production has increased continuously from 1996 (750 million tons) to more than 1.6 billion tons in 2016.
[0006] Aluminum is the most abundant metal in the Earth's crust and the second most produced metal. Its good electrical and thermal conductivity as well as its good, high strength-to-weight ratio make it an excellent material for the electronics and transportation industries. For example, modern aircraft are made of 75-80% aluminum, which is used to manufacture fuselage components, skin materials, and frame and wing structures. The global automotive industry (excluding China) consumed 2.87 million tons of aluminum in 2014, and this figure is expected to reach 4.49 million tons by 2020. Key factors for this growth include the increase in automobile production and the widespread use of aluminum in modern cars. The main reason for this trend is to reduce the weight of vehicles by replacing heavy steel parts, thereby reducing overall fuel consumption. As a result, more and more car parts are made of aluminum: engine radiators, wheels, bumpers, suspension components, engine cylinder blocks, transmission mechanisms, as well as body parts: hoods, doors and frames. As a result, since the 1970s, the share of aluminum in the total weight of an average car has increased from 35kg to 152kg. Experts predict that by 2025, the average aluminum content of a car will reach 250kg.
[0007] Copper is the most commonly used metal in electrical applications due to its high electrical conductivity and low production cost. Copper alloys more easily than any other metal and is therefore widely used as an alloying element for a large number of metals, including aluminum, tin, nickel, steel, and zinc. However, copper is highly susceptible to environmental corrosion.
[0008] Titanium and its alloys have a very favorable strength-to-mass ratio. They are also corrosion-resistant, as a thin and resilient oxide layer forms on their surface. They are mainly used in the aerospace and medical industries, where strength, lightness and corrosion resistance are required. However, the main problem with titanium is its high cost compared to aluminum, copper or steel.
[0009] Zinc is primarily used as a sacrificial coating to protect ferrous materials (iron and steel) from corrosion in ambient atmospheres. Zinc is also used as an alloy and / or alloying element in semi-finished products such as coins, small electrical fuses, anode straps for buried pipelines, and in the manufacture of decorative and functional products such as door handles, marine fittings, pipe assemblies, and screw fasteners. Zinc is water-resistant but is very sensitive to acidic and alkaline environments.
[0010] The most widely used metals mentioned above are susceptible to corrosion and related environmental effects and usually require surface treatment to provide additional corrosion resistance. Commonly used surface treatments include anodizing, conversion coatings, phosphating, and highly cross-linked organic polymer coatings (water-based or solvent-based). These treatments are metal-specific and therefore not suitable for all metal surfaces. In addition, these treatments either do not comply with current environmental regulations or have higher requirements for corrosion resistance, processing simplicity, or cost.
[0011] Inclusion of cross-linking chemicals in a predetermined ratio can reduce the porosity of the coating and improve structural strength and corrosion protection. Examples of cross-linking chemicals include: disilanes, diaminoalkanes, diisocyanates, divinylbenzene, acrylic acid, amides & polyamides, aziridines, benzoguanamines, carbodiimide resins, glycolurils, isocyanates, melamines, polyols, silicon-based compounds, ureas & polyurethanes.
[0012] One of the most important aspects of anticorrosive coating design is the use of environmentally friendly compounds in the composition. While many attempts focusing on waterborne systems have been reported in the literature, hybrid sol-gel coatings have received special attention over the past few decades as they can be used as a pretreatment layer or as a primer for different metal alloys. Transparent zirconium-based hybrid sol-gel coatings are a promising alternative to the above-mentioned chromate-based systems, which have excellent potential to provide a completely corrosion-resistant, durable and aesthetic system for the above-mentioned metals.
[0013] Key requirements for protective coatings designed to protect metals are high corrosion resistance, including barrier and / or corrosion inhibition properties, high adhesion to the substrate being protected, and heat resistance and UV resistance in neutral and acidic humidity. Known metal coatings do not meet all of these key requirements. The present invention solves this problem.
[0014] On the other hand, the present invention solves the problem of adhesion between two surface layers and the problem of introducing multifunctionality into sol-gel coatings. One of the core challenges when using standard hybrid sol-gel to directly replace chrome-based coatings on bare metal is the poor adhesion between the two surfaces. Due to this poor adhesion, the anti-corrosion performance is severely affected and delamination is observed after short exposure in corrosive environments.
[0015] The present invention seeks to alleviate the disadvantages of known surface coatings, particularly metal surface coatings, including metal coated plastics. SUMMARY OF THE INVENTION
[0017] Therefore, one aspect of the present invention provides a composition as claimed in claim 1 for forming a nanostructured hybrid sol-gel coating for surface protection. The present invention also provides a nanostructured hybrid sol-gel coating and a method for preparing the nanostructured hybrid sol-gel coating as described in other independent claims of the appended claims.
[0018] The present invention provides a composition for forming a multifunctional hybrid sol-gel coating, the composition of the present invention comprising a combination of a methacrylate silane and a zirconium alkoxide complex for protecting metal surfaces from environmental degradation including corrosion, UV exposure, heat resistance, acid weathering and moisture.
[0019] An advantage of the present invention is that it provides a material particularly suitable for coating metal surfaces, including metal-coated plastics. The present invention is particularly suitable for forming coatings on metal surfaces, however it should be understood that the coatings of the present invention can also be used to coat plastic surfaces, including metal-coated plastic surfaces and 3D printed / additively manufactured products.
[0020] An advantage of the compositions and coatings of the present invention is that they provide clear, zirconium-based hybrid sol-gel coatings that provide a complete corrosion protection, durable and aesthetic system for the above-mentioned metals.
[0021] The coatings for protecting metals of the present invention have the advantages of high corrosion resistance, including barrier and / or corrosion inhibition, high adhesion to the substrate to be protected, and heat resistance and UV resistance in neutral and acidic humidity. The coatings formed from the compositions of the present invention have the significant advantage of achieving and providing all of these properties simultaneously by providing a highly dense hybrid sol-gel coating having a surface functionalized with a highly adherent inorganic chemical.
[0022] The present invention provides the use of a sol-gel coating composition as described herein as an anti-corrosion coating suitable for use on metal surfaces.
[0023] The present invention also provides the use of the chelate as described herein as an anti-corrosion coating suitable for metal surfaces.
[0024] The present invention provides highly dense hybrid sol-gel coatings whose surfaces are functionalized with high adhesion inorganic chemicals.
[0025] The present invention also provides a method for preparing the hybrid sol-gel coating of the present invention, and provides preferred embodiments of the hybrid sol-gel coating and the preparation method thereof, respectively.
[0026] One advantage of the present invention is that it simultaneously exhibits high corrosion resistance properties, including barrier and / or corrosion inhibition, and high adhesion to the substrate to be protected, as well as heat resistance and UV resistance in neutral and acidic humidity.
[0027] Zirconium (Zr) Chemistry
[0028] The organometallic precursor of the present invention is preferably a transition metal precursor, and most preferably a precursor comprising zirconium. The zirconium precursor may be zirconium (VI) propoxide (Zr(OPr) 4 ).
[0029] In one embodiment, the organometallic precursor is a transition metal precursor, such as a zirconium precursor. The inclusion of a zirconium precursor is understood to improve the adhesion of the coating, and / or the pH stability of the coating, and / or the film hardness. The zirconium precursor of choice is zirconium (VI) n-propoxide (Zr(OPr) 4 )(70 wt% 2-propanol). The zirconium precursor is more reactive towards water than the organosilane precursor. Therefore, in order to avoid the formation of unwanted zirconium oxide precipitates, it is necessary to chelate the Zr(OPr) 4 , reducing the binding possibilities from 4 to 2 (or 1) sites. This can be achieved by using bidentate (or monodentate) ligands in equimolar ratios. Typical chelates include carboxylic acids such as methacrylic acid and acetic acid (as well as (3-aminopropyl)triethoxysilane). When MAPTMS is used as a host matrix former, methacrylic acid is the preferred ligand because it contains methacrylic acid functional groups, which can further polymerize with the organic counterpart of the silane and minimize the porosity of the coating.
[0030] Tridentate silane
[0031] In another aspect of the present invention, the problem of poor adhesion when using sol-gel coatings is solved. The most popular known strategy to increase the adhesion of organics and sol-gel coatings on metals is through mechanical interlocking through an anodic layer deposited on the metal. The present invention also provides tridentate silanes, which will enable the irreversible fixation of sol-gel nanomaterials on the metal surface, while also facilitating the densification process of the coating on the metal substrate. In this regard, the present invention therefore also provides a method, such as Figure 3As shown in Figure 1, sol-gel coatings were prepared using the following substances as precursors: MAPTMS (3-(trimethoxysilyl)propyl methacrylate), BTSPA (bis[3-(trimethoxysilyl)propyl]amine), APTES (3-(aminopropyl)triethoxysilane) or MAAH (methacrylic acid), and ZPO (zirconium(IV) propoxide), where the catalyst was HNO 3 (nitric acid), the networked silane precursor is MAPTES, the interlocking transition metal is ZPO, the kinetic silane is APTES, and the tridentate silane is BTSPA.
[0032] APTES forms a coordination bond with zirconium propoxide by sharing the free electron pair on the nitrogen atom with the d free orbital of the zirconium atom ( Figure 6 ). This has the effect of increasing steric hindrance around the silicon atoms, thereby reducing their reactivity in liquids in the presence of strongly hydrophilic species such as water. Importantly, the main benefit is the provision of anchoring points for MAPTMS via a condensation reaction between APTES and residual Si-OH groups located on MAPTMS, where the groups are activated by aqueous nitric acid used as a catalyst, thereby acting as network interlockers.
[0033] BTSPA is included as a tridentate silane sol-gel reactive precursor and is used in transition metal interlocked silane nanomaterial systems. The tridentate silane is first activated by the catalyst and then added at the end of the sol-gel synthesis to act as a surface modifier for interlocked nanomaterials, such as Figure 6 This surface functionalization has a beneficial effect on the further condensation of the nanomaterial and its irreversible anchoring on the metal substrate: the tridentate silane has six reactive silanol groups that can bind (which can simultaneously bind to the silane component of the interlocking silane nanomaterial system and the metal surface), as well as amino groups that can bind to the zirconium atom similar to APTES. Therefore, BTSPA effectively acts as a tridentate system, such as Figure 7 shown.
[0034] In a first aspect, the present invention provides a composition for forming a novel highly dense hybrid sol-gel coating based on the interconnectivity of two hybrid networks formed by a methacrylic silane, preferably 3-(trimethoxysilyl)propyl methacrylate (MAPTMS), and a transition metal complex, preferably a zirconium complex, as shown in the accompanying drawings of the specification. Figure 1 shown.
[0035] In a second aspect, the present invention provides the development and use of novel highly dense hybrid sol-gel coatings based on the interconnectivity of two hybrid networks formed by the combination of different combinations and ratios of silane precursors (PhTEOS (phenyltriethoxysilane) / TEOS (tetraethyl orthosilicate) / MAPTMS) with a transition metal complex, preferably zirconium (and optionally TIOP (titanium isopropoxide)), a complex chelated with MAAH or APTES, and optionally an additive selected from silica gel, BTSPA and / or BTA (benzotriazole). The different combinations and ratios of the ingredients of the sol-gel composition are summarized in Table 1 and the method of forming the sol-gel coating according to the second aspect of the invention is summarized in Table 1. Figure 2 Overview.
[0036] Preferably, the present invention provides highly dense hybrid sol-gel coatings based on the interconnectivity of two hybrid networks formed by methacrylate silanes and transition metal complexes.
[0037] In a first aspect of the invention, tetraethyl orthosilicate (TEOS) may be added in the final stage of the method for forming the coating of the invention to improve the ability of the Si / Zr sol to form a dense coating. TEOS substantially covers the colloidal Si / Zr and improves their ability to bind together. It has been found that the addition of TEOS can achieve improved coating formation.
[0038] In a second aspect of the invention, additives (BTA, BTSPA, silica gel, etc.) may be added at the end of the process of forming the coating of the invention to improve the properties of the resulting sol-gel coating.
[0039]
[0040]
[0041] Chemicals and abbreviations used in sol-gel compositions
[0042] The present invention provides highly dense hybrid sol-gel coatings based on the interconnectivity of two hybrid networks formed by methacrylate silanes and transition metal complexes.
[0043] Therefore, the present invention provides a hybrid sol-gel coating composition comprising the following:
[0044] (a) an organosilane or a mixture of organosilanes, comprising at least an organosilane precursor MAPTMS (3-(trimethoxysilyl)propyl methacrylate);
[0045] (b) a metal complex comprising zirconium and a ligand; and optionally
[0046] (c) Additives and / or solvents.
[0047] Preferably, the composition comprises a catalyst, more preferably, the catalyst comprises HNO 3 .
[0048] Preferably, the additive comprises any one or more selected from the following: BTSPA (bis[3-(trimethoxysilyl)propyl]amine), BTA (benzotriazole), TEOS (tetraethyl orthosilicate), silica gel, or a combination thereof.
[0049] In a preferred embodiment, the additive comprises a corrosion inhibitor, which is preferably BTA;
[0050] Optionally, BTSPA, when used as an additive, promotes adhesion to surfaces by forming a tridentate based interlocking mixed silane sol.
[0051] When used as an additive, TEOS improves the bonding between the silane precursor and the metal complex and has been found to improve coating formation.
[0052] Preferably, the solvent comprises a 1 -C 4 Any one or more of alcohols.
[0053] In a preferred embodiment, the alcohol comprises ethanol.
[0054] Preferably, the ethanol is in the range of 0-25% w / w.
[0055] When silica gel is used as an additive, it is preferably used in the range of 0.25-1.25% w / w.
[0056] Preferably, BTSPA is used in the range of 0.5-10% w / w.
[0057] Preferably, BTA is in the range of 0.2-1.5% w / w.
[0058] Preferably, BTSPA is first treated with 0.1 M HNO 3 (Nitric Acid) Catalysis.
[0059] Preferably, the organosilane comprises a combination selected from one or more organosilane precursors, wherein the organosilane precursor is selected from: PhTEOS (phenyltriethoxysilane), TEOS or MAPTMS, or a combination thereof, more preferably, wherein the methacrylate silane comprises MAPTMS.
[0060] Preferably, the metal complex comprises zirconium and / or titanium, more preferably, wherein the metal complex comprises zirconium (IV) propoxide and / or titanium isopropoxide.
[0061] In one embodiment, titanium isopropoxide is used in conjunction with zirconium (IV) propoxide to improve crosslinking and surface energy.
[0062] Preferably, the metal complex comprises a monodentate or bidentate ligand.
[0063] In a preferred embodiment, the ligand comprises MAAH (methacrylic acid).
[0064] In another embodiment, the ligand comprises APTES ((3-aminopropyl)triethoxysilane).
[0065] In a preferred embodiment, the molar ratio of the composition components comprises a molar ratio of silane precursor:metal complex of 80:20, and more preferably, wherein the composition components comprise a molar ratio of MAPTMS:TEOS:Zr:MAAH of 75:5:10:10.
[0066] Preferably, the molar ratio of the components includes a molar ratio of organosilane precursor:metal complex of 50:50 to 99:1, preferably 80:20.
[0067] In another aspect, the present invention also provides a method for preparing a mixed sol-gel composition, the method comprising the following steps:
[0068] (a) hydrolyzing a silane precursor;
[0069] (b) chelating metals to form metal complexes;
[0070] (c) combining an organosilane precursor with a metal complex to form an intermediate sol;
[0071] (d) hydrolyzing the intermediate sol to form a pre-final sol, and
[0072] (e) optionally adding additives and / or solvents to form a final sol.
[0073] It should be understood that in one embodiment, a "pre-finished" sol can be used as a composition for coating on a substrate.
[0074] In a preferred embodiment, in step (a), the silane precursor is HNO 3 The aqueous solution is hydrolyzed, and HNO 3 The solution was added dropwise to the mixture.
[0075] In a preferred embodiment, in step (d), the intermediate sol is hydrolyzed with deionized water.
[0076] The present invention also provides a coating formed from the composition of the present invention.
[0077] The present invention also provides a coated substrate, which is prepared by coating the composition of the present invention onto a surface.
[0078] In a first aspect, the present invention provides a sol-gel coating composition comprising a hydrolyzed organosilane, an organometallic precursor and a ligand, wherein the ligand is a chelating agent for the organometallic precursor, and wherein the ratio of the organosilane to the zirconium complex is 8: 2. The organosilane comprises methacryloxypropyltrimethoxysilane (MAPTMS) and / or tetraethyl orthosilicate (TEOS).
[0079] Preferably, the composition comprises a molar ratio of 75:5:20:20 of MAPTMS:TEOS:Zr:MAAH. This can also be expressed as a molar ratio of 80:20 of silane:zirconium.
[0080] Preferred ratios in the composition:
[0081] The ratios used are:
[0082] MAPTMS:TEOS:Zr:MAAH is 75:5:10:10;
[0083] Or this can also be expressed as:
[0084] Silane:zirconium is 80:20.
[0085] In a second aspect, the present invention also provides Figure 2 Flow chart of the preparation of the sol-gel composition.
[0086] Hybrid sol-gel coatings based on a combination of a silane network former and a transition metal network interlocker, stabilized by a reactive silane and a tridentate silane, can be prepared according to the method of the second aspect of the invention.
[0087] The present invention will now be described in more detail with reference to the accompanying drawings and the following examples.
[0088] Instruction Manual
[0089] Figure 1 It is a schematic diagram of the steps of the preparation method of the multifunctional mixed sol-gel coating according to the first aspect of the present invention;
[0090] Figure 2 The sol-gel synthesis process of the second aspect of the present invention;
[0091] Figure 3is a flow chart outlining a method for preparing an interlocking tridentate hybrid sol-gel material according to a second aspect of the present invention;
[0092] Figure 4 is a flow chart outlining the method for preparing the sol-gel coating of the second aspect of the present invention, particularly the F006 composition;
[0093] Figure 5 is a flow chart outlining a method for preparing a sol-gel coating according to the first and second aspects of the present invention;
[0094] Figure 6 is a schematic diagram showing the coordination reaction of APTES and zirconium propoxide;
[0095] Figure 7 is a schematic diagram showing the interlocking nanomaterial reaction of tridentate silane with metal surface;
[0096] Figure 8 (a), (b), (c) and (d) show the sol-gel compositions of F001-F004 of the following examples ( Figure 8 (a)-F001, Figure 8 (b)-F002), Figure 8 (c)-F003, Figure 8 (d) -F004) viscosity curve at different ethanol (EtOH) dilutions over time;
[0097] Fig. 9 (a), (b), (c), (d) and (e) show the viscosity of the sol-gel composition of F005 as a function of time at different ethanol (EtOH) dilutions and BTSPA concentrations ((a) 0.0 wt BTSPA, (b) 0.5% wt BTSPA, (c) 1.0% wt BTSPA, (d) 2.5% wt BTSPA, (e) 5.0% wt BTSPA);
[0098] Fig.10 (a), (b), (c), and (d) show the TGA weight loss traces on four sol-gel compositions ((a) F001, (b) F002, (c) F003, (d) F004), respectively;
[0099] Fig.11 (a), (b), (c), and (d) are the heat flow traces of TGA on four sol-gel compositions ((a) F001, (b) F002, (c) F003, (d) F004), respectively;
[0100] Fig.12Shows the time required for the pendulum to damp from 6° to 3°. Higher values indicate harder coatings. Substrate: R-ICF Q-Panel;
[0101] Fig.13 Water contact angles of compositions F001-F005 are shown. Substrate: R-ICF Q-panel;
[0102] Fig.14 R-ICF Q-panel coated with F001 after 24 hours in NSS. Each row is a different immersion speed. Each column represents the number of sol-gel coatings;
[0103] Fig.15 R-ICF Q-panel coated with F002 after 24 hours in NSS. Each row is a different immersion speed. Each column represents the number of sol-gel coatings;
[0104] Fig.16 R-ICF Q-panel coated with F003 after 24 hours in NSS. Each row is a different immersion speed. Each column represents the number of sol-gel coatings;
[0105] Fig.17 R-ICF Q-panel coated with F004 after 24 hours in NSS. Each row is a different immersion speed. Each column represents the number of sol-gel coatings;
[0106] Fig.18 (a), (b) and (c) show mild steel pretreated with third-party silane (3PS) coatings after 336 hours in NSS: (a) 3PS only, (b) 3PS & sol-gel system 'E' (F001), (c) 3PS & sol-gel system 'J' (F005 & F001);
[0107] Fig.19 (a) and (b) show galvanized steel pretreated with third-party silane (3PS) after 336 hours in NSS: (a) 3PS only, (b) 3PS & sol-gel system 'J' (F005 & F001);
[0108] Fig. 20 (a), (b), (c), (d) and (e) show aluminum 6000 series alloys after 336 hours in NSS: (a) uncoated, (b) sol-gel system ‘D’ (F001x2), (c) sol-gel system ‘F’ (F003x2), (d) sol-gel system ‘I’ (F005), (e) sol-gel system ‘J’ (F005&F001);
[0109] Fig.21(a), (b), (c), (d) and (e) show aluminum 6000 series alloys pretreated with third party silane (3PS) after 336 hours in NSS: (a) 3PS only, (b) 3PS sol-gel system 'A' (F001), (c) 3PS & sol-gel system 'E' (F003), (d) 3PS & sol-gel system 'I' (F005), (e) 3PS & sol-gel system 'J' (F005 & F001);
[0110] Fig. 22 Aluminum 2024T3 with various anodized surface treatments and sol-gel sealing after 500 h in NSS;
[0111] Fig.23 (a), (b), and (c) are SEM images of: an uncoated 3D printed part (a), a sol-gel coated part (b), and a 3D printed part that was scratched and then etched in hydrofluoric acid (HF) before coating (c);
[0112] Fig.24 (a), (b), (c), (d), (e) and (f) are energy dispersive X-ray (EDX) of sol-gel coated 3D printed parts: (a) corresponding SEM image, (b) silicon, (c) zirconium top right, (d) aluminum, (e) titanium middle bottom, (f) EDX spectrum.
[0113] refer to Figure 1 The method of the first aspect of the present invention will now be described by means of a flow chart:
[0114] (a) Organosilane hydrolysis to form silane sol
[0115] By using HNO with a volume ratio of 1:0.75 3 The first hydrolysis of the organosilane was carried out by hydrolyzing the organosilane MAPTMS with a 0.01M aqueous solution (below this ratio, precipitation of zirconium species occurred during the second hydrolysis). Since MAPTMS and water are immiscible, the hydrolysis was carried out in a heterogeneous phase. After stirring for 20 min, the amount of methanol generated was sufficient to mix all the substances present in the solution;
[0116] (b) Zirconium chelation to form a zirconium complex
[0117] MAAH was added dropwise to ZPO at a molar ratio of 1:1. MAAH reacted with ZPO reagent to form modified zirconium alkoxide Zr(OPr) 4-2x (MAA)x, wherein MAA is the deprotonated form of MAAH;
[0118] (c) Organosilane zirconium combination to form Si / Zr sol
[0119] After a predetermined time has elapsed, preferably about 45 minutes, the partially hydrolyzed MAPTMS is slowly added to the zirconate complex. This mixture is characterized by an increase in temperature, indicating the formation of an irreversible chemical bond;
[0120] (d) Hydrolysis to form a pre-final sol
[0121] After another predetermined time has passed, preferably about 2 minutes, water is then added to the mixture. After a predetermined hydrolysis time, preferably about 45 minutes, the second hydrolysis produces a stable and uniform sol; and
[0122] (e) Formation of the final sol
[0123] TEOS (0.33 g) was added to the pre-final sol to form the final sol.
[0124] Example 1
[0125]
[0126]
[0127] In all examples, methacrylic acid (MAAH) was used as the chelating agent.
[0128] The following methods are implemented:
[0129] (a) Hydrolysis of organosilane to form silane sol
[0130] By using HNO with a volume ratio of 1:0.75 3 The organosilane hydrolysis was achieved by hydrolyzing MAPTMS (61.22 g) with a 0.01 M aqueous solution (below this ratio, precipitation of zirconium species occurred during the second hydrolysis). Since MAPTMS and water are immiscible, the hydrolysis was carried out in a heterogeneous manner. After stirring for 20 min, the amount of methanol generated was sufficient to mix all the substances present in the solution.
[0131] (b) Zirconium chelation to form a zirconium complex
[0132] MAAH (5.30 g) was added dropwise to ZPO (28.25 g) at a molar ratio of 1:1. MAAH reacted with the ZPO reagent to form a modified zirconium alkoxide Zr(OPr) 4-2X (MAA) X , where MAA is the deprotonated form of MAAH.
[0133] (c) Organosilane zirconium combination to form Si / Zr sol
[0134] After 45 min, the partially hydrolyzed MAPTMS was slowly added to the zirconate complex. This mixture was characterized by a temperature increase, indicating the formation of an irreversible chemical bond.
[0135] (d) Hydrolysis to form a pre-final sol
[0136] After another predetermined time, about 2 min, water was then added to the mixture. After a hydrolysis time of about 45 min, this second hydrolysis produced a stable and homogeneous sol.
[0137] (e) Formation of the final sol
[0138] TEOS (0.33 g) was added to the pre-final sol to form a final sol with a final molar ratio of 75:5:20:20 MAPTMS:TEOS:Zr:MAAH, or 80:20 silane:zirconium.
[0139] Example 2
[0140] The method steps are carried out as in Example 1, and the amounts used are as follows:
[0141]
[0142] Example 3
[0143] The method steps are carried out as in Example 1, and the amounts used are as follows:
[0144]
[0145] The coatings of the present invention provide surprisingly effective protection of metal coatings and meet all of the above mentioned coating requirements.
[0146] According to a second aspect of the present invention, and Figure 2 (and Figure 4 ), 6 sol-gel compositions (F001-F006) were prepared as follows:
[0147] The silane precursor (A) was first mixed with a magnetic stirrer until homogeneous. Next, 0.1 M nitric acid in deionized water was added to the silane mixture to hydrolyze the alkoxide functional groups. At this stage, 25% of the alkoxide groups were hydrolyzed. 0.1 M HNO 3 catalyst to avoid shocking the silane mixture.
[0148] - At the same time, the transition metal (ZPO and / or TIOP) chelates with methacrylic acid to form a metal complex (B) (this is not the case for F005, where APTES is used). Methacrylic acid chelates the x2 alkoxide functional groups in ZPO.
[0149] After stirring the silane precursor (A) and the metal complex (B) separately for 45 min, the silane precursor was added to the metal complex and stirred for another 2 min. Initially, the silane was added dropwise to avoid any potential precipitation.
[0150] When (A) and (B) were mixed, a second hydrolysis was performed. For this hydrolysis, deionized water was added to achieve a total hydrolysis of 50% of the alkoxide groups in the sol-gel.
[0151] If applicable, any additives (e.g. silica gel, BTSPA, BTA) and / or solvents (e.g. ethanol) are added at this stage.
[0152] The final sol-gel mixture was stirred for an additional 45 min.
[0153] About the synthesis of composition F005:
[0154] It is very important to add the zirconium isopropoxide (ZPO) to the APTES (and not the other way around). Note that this prevents the APTES from precipitating out of the mixture.
[0155] BTSPA can be catalyzed (or activated) with 0.1 M nitric acid in deionized water before addition to the sol-gel. A 10% hydrolysis level was found to be very stable over time. Higher hydrolysis levels will cause the BTSPA to gel within a few hours.
[0156] Activated BTSPA should be added to the sol-gel just before the part is to be coated. This is especially important for high concentrations of BTSPA (e.g., 5.0% by weight) because the sol-gel will gel rapidly (<2 hours) and continue to increase in viscosity.
[0157] Prior to dip coating, the sol-gel was filtered using a 1.0 micron PTFE syringe filter to remove any large agglomerates or contaminants. If desired, the sol-gel may be diluted with a solvent such as ethanol or isopropanol to reduce viscosity and extend shelf life.
[0158] Table 1 briefly describes each composition, each composition is divided into three main components; 1) a mixture of silane precursors, 2) a metal complex, and 3) an additive. The full chemical names described by the abbreviations used in Table 1 are found in the "Summary of the Invention" section.
[0159] Table 1: Sol-gel compositions investigated in this study.
[0160]
[0161]
[0162] Compositions F001 to F003 were developed as hard, hydrophobic and scratch resistant coatings, as well as aesthetically pleasing surface finishes. F004 was developed as a corrosion resistant sealant for anodized aluminum alloys. Composition F005 was intended to have adhesion promoting properties. Composition 6 is both a corrosion resistant sealant and an adhesion promoter.
[0163] Sol-gel composition F001-F006
[0164] A more detailed breakdown of each sol-gel composition (F001 to F006) is shown in Tables 2 to 41. Each composition comprises a mixture of a silane precursor, a metal complex and, if applicable, an additive to impart additional functionality, and a solvent, if applicable. The percentages of additives are expressed as % w / w of the wet sol-gel to which they were added. The tables corresponding to the properties of the sol-gel compositions tested are marked with an asterisk (*):
[0165] Table 2: Sol-Gel F001 composition
[0166]
[0167] Table 3: Sol-Gel F001 composition
[0168]
[0169] Table 4: Sol-Gel F001 composition
[0170]
[0171] Table 5: Composition of Sol-Gel F001
[0172]
[0173] Table 6: Sol-Gel F001* Composition
[0174]
[0175] Table 7: Sol-Gel F001 composition
[0176]
[0177] Table 8: Sol-Gel F002* Composition
[0178]
[0179] Table 9: Sol-Gel F002 composition
[0180]
[0181]
[0182] Table 10: Sol-Gel F003 composition
[0183]
[0184] Table 11: Sol-Gel F003 composition
[0185]
[0186] Table 12: Sol-Gel F003 composition
[0187]
[0188]
[0189] Table 13: Sol-Gel F003 Composition
[0190]
[0191] Table 14: Sol-Gel F003 Composition
[0192]
[0193] Table 15: Sol-Gel F003 Composition
[0194]
[0195]
[0196] Table 16: Sol-Gel F003* Composition
[0197]
[0198] Table 17: Sol-Gel F003 Composition
[0199]
[0200] Table 18: Sol-Gel F004 composition
[0201]
[0202] Table 19: Sol-Gel F004 composition
[0203]
[0204] Table 20: Sol-Gel F004* Composition
[0205]
[0206] Table 21: Sol-Gel F004 composition
[0207]
[0208]
[0209] Table 22: Sol-Gel F004 composition
[0210]
[0211] Table 23: Sol-Gel F004 composition
[0212]
[0213] Table 24: Sol-Gel F004 Composition
[0214]
[0215]
[0216] Table 25: Sol-Gel F004 composition
[0217]
[0218] Table 26: Sol-Gel F005 Composition
[0219]
[0220] Table 27: Sol-Gel F005 Composition
[0221]
[0222]
[0223] Table 28: Sol-Gel F005* Composition
[0224]
[0225] Table 29: Sol-Gel F005 Composition
[0226]
[0227] Table 30: Sol-Gel F005 composition
[0228]
[0229]
[0230] Table 31: Sol-Gel F005 composition
[0231]
[0232] Table 32: Sol-Gel F005 Composition
[0233]
[0234] Table 33: Sol-Gel F005 Composition
[0235]
[0236]
[0237] Table 34: Sol-Gel F006 Composition
[0238]
[0239] Table 35: Sol-Gel F006 Composition
[0240]
[0241] Table 36: Sol-Gel F006 Composition
[0242]
[0243]
[0244] Table 37: Sol-Gel F006 Composition
[0245]
[0246] Table 38: Sol-Gel F006 Composition
[0247]
[0248] Table 39: Sol-Gel F006 Composition
[0249]
[0250] Table 40: Sol-Gel F006 Composition
[0251]
[0252] Table 41: Sol-Gel F006 Composition
[0253]
[0254] Testing of F001-F005 compositions on metal substrates
[0255] Several metal substrates (primarily aluminum "A", mild steel "R" and "R-ICF" 5 substrates) were used to test the sol-gel F001-F005 compositions. They were all purchased from Q-Lab & Amari. Table 41 summarizes the metal substrate types and surface finishes from Q-Lab. The Q panels were prepared using iron phosphate pretreatment and dip coated as received. However, the bare aluminum "A" and mild steel "R" were degreased using a 0.5M sodium hydroxide (NaOH) solution in deionized water, followed by rinsing with deionized water and isopropyl alcohol (IPA). The panels were then dried with hot air before dip coating.
[0256] 2024T3 grade aluminum alloy panels (cut into 6” x 3” x 1.5mm thickness) were purchased from Amari. The substrate was used for anodizing with sol-gel as a sealant. The panels were anodized in sulfuric acid before sol-gel coating. As part of the anodizing process, the aluminum alloy was cleaned and deoxidized (Socomore A1859 / A1806) in an alkaline degreaser (Socomore A3432) before anodizing. After anodizing, the panels were soaked in IPA for a few minutes to remove the residual water in the anodic layer. Finally, they were blown dry with hot air and then the IPA solvent was removed. At this stage, the panels were dip coated in sol-gel. The anodized panels were allowed to stay in the sol-gel for 2.5 minutes to allow the sol-gel to penetrate into the anodic layer.
[0257] Table 42: Metal substrates purchased from Q-Lab.
[0258] Q-Lab Product Code describe A Bare aluminum 3003H14 R 1008 / 1010 grade steel with a matte polished finish R-ICF "R" with iron phosphate conversion coating
[0259] Experimental methods and sample testing
[0260] The following experimental methods were used to test the compositions [F001]-[F005] and the prepared samples. Where applicable, reference is made to the test standards.
[0261] Viscosity
[0262] The viscosity of the sol-gel was measured using an AND SV-10 viscometer. Figure 7 As shown. About 35-45 ml of sol-gel sample is placed in the container. After the system is started, it is allowed to run for about 20 seconds to reach a steady state. Thereafter, viscosity measurements are taken every 10 seconds until 5 readings are obtained. The viscosity value shown here is the average of these 5 readings.
[0263] Thermogravimetric analysis (TGA)
[0264] TGA was used to gain insight into the curing behavior of different sol-gel compositions. The tests were performed on a Shimadzu DTG 60MTGA. Two different TGA heating profiles were used. The first was a dynamic scan from 25°C to 250°C at a rate of 5°C / min. This was performed on liquid sol-gel as well as pre-cured samples. The second was a simulated cure cycle, replicating the cure profile of dip-coated parts cured in a conventional oven. In this case, the sol-gel was heated at a rate of 10°C / min to the curing temperature (usually between 100°C and 160°C, depending on the composition) and then held for 60min. In all cases, the weight of the liquid sol-gel sample was approximately 20-30mg.
[0265] Pendulum Damping Test
[0266] Pendulum damping test according to ISO 1522-2006. The pendulum test was used to indicate the hardness of each sol-gel coating. The softer the coating, the faster the pendulum oscillations decayed (i.e., the fewer swings).
[0267] Pencil hardness test
[0268] Pencil hardness testing is performed according to ISO 15184-2012 (Determination of film hardness by pencil test). This particular test is a common industry method used to rank the relative hardness of different coatings.
[0269] Water contact angle
[0270] Using First Ten The water contact angle (WCA) is determined using the (FTA) system. Five drops of deionized water are used for each coating sample. The WCA values presented in this report are the average of five measurements. Lower contact angles (<90°) indicate hydrophilic coatings that may be suitable for subsequent painting or adhesive bonding. Higher contact angles (>90°) indicate hydrophobic coatings that may be suitable for self-cleaning solutions.
[0271] Dip coating
[0272] The samples were dip coated using the Bungard RDC 21-K system. The Q-panel samples were secured using alligator clips and dipped into a tank containing the sol-gel at a constant speed. The panels were kept in the sol-gel for up to 20 seconds (longer for anodized panels) and then removed at a constant speed. The removal speed was varied to control the final coating thickness and typically ranged from 50 mm / min for thin coatings (<5 μm) to 500 mm / min for thicker coatings (10-20 μm).
[0273] Curing
[0274] After dip coating, the samples were cured in an air circulating oven at the desired temperature. The temperature varied depending on the sol-gel composition. F001-F003 and F005 were typically cured at 140°C for 1 hour, while F004 was cured at 120°C for 2 hours.
[0275] Neutral salt spray
[0276] Accelerated corrosion testing was performed in neutral salt spray (NSS). The NSS chamber was maintained in accordance with ISO 9227:2017. The dip coated and cured samples were sealed on one face with packaging tape. The back face and edges were further sealed with electrical insulating tape. This was to ensure that only the front face of the sample was exposed to the corrosive environment. For this report, the samples were monitored for a maximum of 672 hours (4 weeks).
[0277] Viscosity results
[0278] The viscosity of the sol-gel has a significant effect on the coating thickness obtained after dip coating. The study was divided between compositions F001-F004 and F005 respectively. This is because the effect of BTSPA concentration was also considered as part of the dilution study.
[0279] Compositions F001-F004 were prepared under three different ethanol (EtOH) dilutions. They are 0%, 10% and 25%wt ethanol. Adding solvent helps to reduce viscosity and extend the shelf life of sol-gel. Viscosity was monitored for up to 84 days (12 weeks) after synthesis. Compositions F001-F004 generally show viscosity increases over time when each dilution. Compositions with the highest metal complex molar concentration (i.e. F001 and F004) show that they start with the highest viscosity and increase the fastest over time. When diluted with 25%wt ethanol, all sol-gels remain relatively stable over time, and the viscosity remains at about 20-40mPa.s.
[0280] Composition F005 was diluted with 4 different concentrations of ethanol, 0%, 10%, 25% and 50% wt ethanol. Five different concentrations of BTSPA levels were also considered, 0.0%, 0.5%, 1.0%, 2.5% and 5.0% wt BTSPA. The viscosity was monitored for up to 84 days (12 weeks) or until the viscosity reached about 100 mPa.s. At this viscosity level, the sol-gel was considered to have expired. Fig. 9The relationship between viscosity and sol-gel age using different EtOH dilution levels and BTSPA concentrations is shown. As observed for F001-F004, it was found that ethanol levels reduced the viscosity of the sol-gel and extended the shelf life (i.e., prevented the viscosity from increasing rapidly over time). Over time, dilutions of 25% or 50% EtOH produced sol-gels that were relatively stable over time. The concentration of BTSPA had a significant effect on the viscosity of the sol-gel. At high concentrations of BTSPA and low concentrations of EtOH dilution, viscosity increased rapidly over time.
[0281] Thermogravimetric analysis (TGA)
[0282] TGA experiments were performed on liquid sol-gel samples to determine the curing behavior at different curing temperatures ranging from 100-160°C. A simulated curing cycle (SCC) was programmed into the TGA, which included a temperature ramp to the curing temperature (i.e., 100, 120, 140, or 160°C) at a rate of 10°C / min, followed by a hold (or dwell) at the curing temperature for 60 min. For this series of tests, the sol-gel was undiluted. Fig.14 The weight loss trajectories for the four compositions at different curing temperatures are shown. It is particularly noteworthy that a 60 min cure cycle at either 100°C or 120°C was insufficient to achieve full cure for compositions F001, F002 and F003. It can be seen that the same level of weight loss was not achieved as for the sol-gel cured at 160°C for 60 min. The same weight loss could have been achieved if a longer cure time was used. However, this would likely require an excessively long cure time.
[0283] Fig.11 Shows the Fig.10 Heat flow trajectory of the same TGA experiment shown in . All compositions and curing temperatures show a clear endothermic peak at the beginning of the simulated curing cycle (0-10min on the x-axis). This is related to the flash evaporation of volatile organic compounds (VOCs) in the sol-gel composition. At 10-20min, several peaks may be related to the formation of the network and the densification of the sol-gel. When the sol-gel is cured at lower temperatures, the intensity of these peaks is not so obvious. This indicates that even though most of the VOCs may have been removed at lower curing temperatures, the sol-gel network may not have been fully cured or condensed.
[0284] Fig.10 and Fig.11 The results shown in show that a cure cycle of 140°C for 60 min is sufficient for compositions F001, F002 and F003, while a cure cycle of 120°C for 120 min can be used for F004.
[0285] TGA experiments have not been performed on composition F005. However, given the relatively similar silane chemistry of F004 (ie, MAPTMS & ZPO), a 120°C, 120 min cure cycle was also used for F005.
[0286] Pendulum Damping Test
[0287] Pendulum damping tests were performed on the cured samples. The test results are presented using R-ICF substrate (mild steel pretreated with iron phosphate) purchased from Q-Lab. The immersion speed for all samples was set to 100 mm / min. The results are shown in Fig.16 As shown, compositions F001-F004 are all in the 180-195 second range, with the oscillation decreasing from 6° to 3°. Composition F003 is the hardest, followed by F004, while F001 and F003 are the softest of the four. F005 is significantly softer than the other four compositions, with a time of 165 seconds. This indicates that it is a softer coating, likely due to the use of APTES instead of MAAH during the synthesis process.
[0288] Pencil hardness test
[0289] The pencil hardness test results for each of the four sol-gel compositions are shown in Table 43. The sol-gel coatings were applied to aluminum "A" specification Q panels. "Pencil Hardness" refers to a specific pencil that does not mark the coating. "Plastic Deformation" is the pencil hardness that produces a mark on the coating. "Cohesive Failure" is the hardness that causes the coating to fall off. Note that "Plastic Deformation" and "Cohesive Failure" can occur at the same pencil hardness value. The results show that the pencil hardness test has difficulty distinguishing between different coatings compared to the pendulum damping test. The only significant difference is that F004 causes "Cohesive Failure" at a slightly higher hardness (3H instead of 2H).
[0290] Table 43: Pencil hardness test results of different compositions.
[0291] Composition Pencil hardness Plastic deformation Cohesive failure F001 H 2H 2H F002 H 2H 2H F003 H 2H 2H F004 H 2H 3H F005 TBC TBC TBC
[0292] Water Contact Angle (WCA)
[0293] The water contact angle results are as follows Fig.13 As shown. The contact angles of all compositions were less than 90°, indicating that the surfaces of all compositions were slightly hydrophilic. The three sol-gels containing PhTEOS (i.e., F001-F003) had the highest contact angles compared to F004 or F005. Composition F005 had the lowest contact angle of all the sol-gels studied. This is believed to be due to the use of APTES and BTSPA, which are known to be highly reactive, in the sol-gel compositions.
[0294] Neutral Salt Spray (NSS) Test
[0295] Various studies have been conducted on the performance of sol-gel coatings in neutral salt spray (NSS) environments. The individual studies were separated by substrate type and sol-gel composition.
[0296] R-ICF Q panels (mild steel pre-treated with iron phosphate) and F001-F004
[0297] The corrosion protection performance is tested as follows:
[0298] The sol-gel compositions (F001-F004) on the substrate were evaluated at different immersion speeds (100, 250 and 500 mm / min) and different numbers of coatings (x1, x2 and x3). The goal was to determine whether thicker sol-gel coatings or multi-coating systems would improve the corrosion protection level of NSS. In this study, R-ICF mild steel Q plates pretreated with iron phosphate were used as is without additional surface treatment.
[0299] Figures 14 to 17 R-ICF Q-panels of compositions F001-F004 after 24 hours in NSS are shown. The photos show that all single coating (x1 dip) systems showed signs of pitting and corrosion after 24 hours. The photos highlighted with a red border show signs of excessive corrosion. Those in orange show some initial signs of corrosion / pitting. The green photos show no signs of damage. Only a few of the multi-dip systems (x2 and x3) did not show any signs of corrosion. Over the course of about 336 hours (2 weeks), all coating systems began to show signs of corrosion. For all four compositions, the x3 coating system at 500mm / min lasted the longest before starting to fail.
[0300] Mild steel, galvanized steel and 6000 series aluminum alloy
[0301] The three substrates used for the sol-gel composition studies were mild steel, galvanized steel, and 6000 series aluminum alloy. Some of these substrates were also provided pre-treated with a third party silane (referred to as 3PS) for use as a baseline comparison.
[0302] As part of this work, a number of different sol-gel systems were investigated. In total, 10 sol-gel systems were considered and are listed in the table. Each system has a unique identification code "A" to "J". As can be seen, several combinations of F001, F003, F004 and F005 were considered. F002 was excluded from this study due to its similarity to F001. Several single and dual coating systems were investigated.
[0303] Table 44: Sol-gel systems studied
[0304]
[0305] The coated panels were evaluated in neutral salt spray for 336 hours (2 weeks). Figures 18 to 21 A photograph of the best performing panel in this study after 336 hours of NSS is shown.For comparison, panels not coated with any of the sol-gel solutions of the present invention are included to highlight the benefits and additional levels of protection obtained by using these systems.
[0306] Fig.18 A series of mild steel panels pre-treated with a third party silane (3PS) are shown. Fig.18 (a) shows that third party silanes alone do not provide adequate protection. Fig.18 (b) and (c) show the sol-gel systems 'E' and 'J' applied to the 3PS surface, respectively. Both solutions remained in good condition after 336 h of NSS exposure.
[0307] Fig.19 All galvanized steel panels are shown that were pre-treated with a third-party silane (3PS). Fig.19 (a) shows that the use of third-party silane alone does not provide adequate protection. Fig.19 (b) shows the sol-gel system 'J' applied on the 3PS surface. After 336 hours NSS, the panel remained in good condition.
[0308] Fig. 20 A substrate material made of a 6000 series aluminum alloy is shown. Fig. 20 (a) shows a panel with no additional surface treatment. As can be seen, the sample exhibits visible excessive corrosion after less than 1 day. Fig. 20 All four sol-gel coated aluminum panels shown in (b), (c), (d), and (e) remained in good condition after 336 h and showed no signs of corrosion.
[0309] Fig.21 6000 series aluminum pretreated with a third-party silane is shown. As before, Fig.21 (a) shows that the use of third-party silanes alone does not provide adequate protection. All four sol-gel coating systems provide excellent corrosion protection up to 336 hours of NSS exposure.
[0310] Anodized Aluminum 2024T3&F004
[0311] The effect of using sol-gel as a sealant after the anodizing process was investigated using aluminum alloy grade AA2024T3. The aluminum panels were anodized in sulfuric acid for 10 or 30 min and then coated as described above. Fig. 22AA2024T3 with five different surface treatment combinations after 500 hours in NSS is shown. As can be seen, the uncoated panel (left) shows signs of excessive corrosion, which is obvious even after a few hours. The next panel (second from the left) was anodized for 30 minutes and was not sealed at all. Although it performs better than the uncoated one, there are obvious signs of pitting. Fig. 22 The middle panel in is the same as the previous panel, but it was heat sealed (HTS) in deionized water at 90°C for 20 minutes. This resulted in significantly better corrosion protection, with almost no signs of pitting or corrosion. The second and rightmost panels from the right were anodized in sulfuric acid for 30 minutes and 10 minutes, respectively, and then sealed with composition F004. Both samples also showed almost no signs of corrosion. This shows that sol-gel can provide the same level of corrosion protection as traditional HTS, while also having the potential for alternative surface treatments (such as gloss).
[0312] Sol-Gel Coatings on Additively Manufactured Parts
[0313] Additive manufacturing opens up new opportunities for producing extremely complex shapes that would otherwise be impossible with traditional manufacturing methods. However, it also brings new coating challenges. Printed parts, especially metal parts, can have thick oxide layers. Line-of-sight coating methods can also make it difficult to coat the entire part.
[0314] The 3D printing material used was grade 23 titanium (G23 / Ti-6Al-4V ELI). But the coating system will be suitable for any 3D printed metal or selected plastic parts. The sol-gel is based on the composition F005. Fig.23 Scanning electron microscope (SEM) images of an uncoated 3D printed part and two coated with F005 sol-gel (one of the samples was pre-etched with hydrofluoric acid) are shown. The area shown on the uncoated part shows Ti G23 powder particles that are loosely sintered together. Fig.23 (b) shows how the sol-gel conforms to the contours of the printed surface. Fig.23 (c) shows a part that was first scratched and HF-etched before coating. Scratching had a significant effect on smoothing the 3D printed surface.
[0315] Fig.24 Energy dispersive X-ray (EDX) analysis of a coated 3D printed part is shown. The elements silicon (Si) and zirconium (Zr) are associated with the sol-gel coating, while titanium (Ti) and aluminum (Al) are associated with the substrate. The elemental map shows that the coating does produce a coating with uniform thickness. This is likely due to the relatively rough nature of the 3D printed surface and the low viscosity of the sol-gel.
[0316] It will of course be understood that various modifications may be made and that the scope of the invention is defined by the appended claims.
Claims
1. A hybrid sol-gel coating composition comprising the following substances: (a) an organosilane or a mixture of organosilanes, comprising at least an organosilane precursor, 3-(trimethoxysilyl)propyl methacrylate (MAPTMS); (b) a metal complex comprising zirconium and a ligand, wherein the ligand is (3-aminopropyl)triethoxysilane (APTES); (c) additives, and optionally solvents; in, The additive includes bis[3-(trimethoxysilyl)propyl]amine (BTSPA) in an amount of 0.5-10% w / w.
2. The composition of claim 1, comprising a catalyst.
3. The composition of claim 2, wherein the catalyst is nitric acid (HNO3).
4. The composition of claim 1, wherein the additive further comprises benzotriazole (BTA).
5. The composition of claim 1, wherein the solvent comprises any one or more alcohols selected from C1-C4 alcohols.
6. The composition of claim 5, wherein the alcohol comprises ethanol (EtOH).
7. The composition of claim 6, wherein the mass proportion of ethanol in the sol-gel coating composition is 0-25% w / w.
8. The composition of claim 4, wherein the mass proportion of BTA in the sol-gel coating composition is 0.2-1.5% w / w.
9. The composition of claim 1, wherein BTSPA is catalyzed using 0.1 M HNO3 prior to addition to the composition.
10. The composition of claim 1, wherein the organosilane comprises phenyltriethoxysilane (PhTEOS) and / or TEOS.
11. The composition of claim 1, wherein the metal complex comprises titanium.
12. The composition of claim 11, wherein the metal complex comprises zirconium (IV) propoxide and / or titanium isopropoxide.
13. The composition of claim 1, wherein the metal complex comprises a monodentate ligand or a bidentate ligand.
14. The composition of claim 13, wherein the ligand comprises methacrylic acid (MAAH).
15. The composition of claim 1, wherein the molar ratio of the organosilane precursor:the metal complex is 50:50 to 99:
1.
16. The composition of claim 15, wherein the molar ratio of the organosilane precursor:the metal complex is 80:
20.
17. A method for preparing the hybrid sol-gel coating composition according to any one of claims 1 to 16, the method comprising the following steps: (a) hydrolyzing an organosilane precursor, wherein the organosilane precursor is 3-(trimethoxysilyl)propyl methacrylate (MAPTMS); (b) chelating a metal to form a metal complex, wherein the metal complex comprises zirconium and a ligand, wherein the ligand is APTES; (c) combining an organosilane precursor with a metal complex to form an intermediate sol; (d) hydrolyzing the intermediate sol to form a pre-final sol, and (e) adding additives and, optionally, solvent to form a final sol, wherein the additives include 0.5-10% w / w of bis[3-(trimethoxysilyl)propyl]amine (BTSPA).
18. The method according to claim 17, wherein in step (a), the organosilane precursor is hydrolyzed with an aqueous solution of HNO3, and wherein the HNO3 solution is added dropwise to the mixture.
19. The method according to claim 17, wherein in step (d), the intermediate sol is hydrolyzed with deionized water.
20. A coating formed from the composition of claim 1.
21. A coated substrate prepared by coating the composition of claim 1 onto a surface.
22. The coated substrate of claim 21, wherein the coated substrate comprises any one or more materials selected from the group consisting of: metal, plastic.
Citation Information
Patent Citations
Organosilane coating compositions and use thereof
CN101925660A
Hybrid metal oxides
US20090163647A1
Antifouling system comprising silicone hydrogel
US20150353741A1